A política imigratória tutelada japonesa e a ação da Bratac Pereira Barreto (SP) 1927-1942 - Soares Filho, Paulo José (2010)
This research analyzes the Japanese immigration politics tutored by Brazil between the late 1920s through the early 1940s. Among our goals, we point out understanding the importance ofthis immigration policy for the formation ofthe city of Pereira Barreto and the mechanisms that the settlers of Brazil arranged as the creation of a series of companies for assistance to immigrants. It is still part of our intentions to see how the Brazilian government, especially during the Vargas Era, behaved on the movement of the Japanese m the colonies of Bastos and Pereira Barreto with the legislation imposed to the Japaneses in this period. It is also our objective to verify the way the delegates of the DEOPS/SP have characterized the Japanese iinmigrants m diverse colonies of the State of São Paulo with more emphasis m the colonies of Bastos and Pereira Barreto, the last standmg out by having a great documentation mvolving the daily life of the city. In the end we will analyze the Japanese m Pereira Barreto highlighting the actions taken by the city regarding the influence they held in various sectors of society formed there, having the support and guidance of the Japanese govemment.